Motif Aktor Lokal dalam Kuota Pencalonan 120 Persen Partai Politik Lokal pada Pemilu 2019 - Nurlaina Nurlaina; Muryanto Amin; Warjio Warjio (PERSPEKTIF, 2021)
This research explains the change in the nomination quota for members of the Provincial DPRD (DPRA) and Regency / City DPRD (DPRK) members for local political parties in the 2019 Election in Aceh Province from a quota of 100 percent to 120 percent based on the number of seats that have been assigned to each electoral district, because the provisions of the LoGA stipulated in the Aceh Qanun are different from the national provisions. The change in the quota cannot be separated from the influence of requests made by DPRA members who are cadres of one of the local political parties. As a political actor at the local level, this request is supported by various motives. To analyze motives, the researchers looked at the reasons local actors asked for changes in nomination quotas. This research is a type of qualitative research by collecting data through interviews, observation and library data, then the data that has been obtained is analyzed by content. Research findings show that actors use an integrative model to get special treatment for local political parties in the 2019 elections, actor actions in achieving preferences, interactions between institutions and instruments or institutional rules, it is found that apart from maintaining the specificity of Aceh, the request for a 120 percent quota for political parties is found. The local background is also motivated by the motive of the interests of actors and their groups, namely becoming incumbent candidates and accommodating many candidates for DPRA and DPRK candidates from the Aceh Party.